The real-time simulation of exposure dose assessment in radioactive environment based on point-kernel method and human phantom. (December 2020) - Liu, Yong-kuo; Yang, Li-qun; Peng, Min-jun; Chao, Nan; Ayodeji, Abiodun; Long, Ze-yu
Abstract: In this paper, a real-time, dynamic radiation dose exposure assessment method is presented based on point-kernel method and stylized computational human phantom, for workers in radioactive environment. The stylized computational phantom is built and transformed into a series of organ-monitoring-points, and the kerma rates free-in-air at organ-monitoring-points are calculated by the point-kernel method. Based on the exposure dose rates of organ-monitoring-points, the absorbed doses of key tissues and organs are calculated, and the effective doses absorbed by the virtual worker is measured during typical decommissioning activities. In addition, to improve the accuracy of result and optimize the proposed method, we account for the influence of protective suit and the human body self-shielding in the calculations. This results in optimized dose assessment method with capability for dynamic calculations of dose exposure for workers in radioactive environment. Highlights: An exposure dose assessment method is proposed based on point-kernel method and stylized phantom. The method can dynamically calculate the exposure dose of workers during the nuclear facility removal process. The method takes into account the influence of the protective suit and the human body self-shielding.